Recycling Nature in Guatemala: a photoessay - Cason O’Connor, Kellie (2015)
O'Connor's current works consist of imagery that addresses the reclamation of nature and the relational aspects between humankind and nature. Her other works include works based in her Appalachian roots, documentary work of the Quiche Mayan culture based in Guatemala, and alternative photographic techniques. Kellie's works have appeared in Lenscratch, Fototazo, Update, and F-Stop Magazines. The images are created primarily through the use of a 4x5 view camera and a medium format rangefinder. All images are created using film. Further information about the artist's works is available at www.kelliecasonoconnor.com.